2017
DOI: 10.17523/bia.v74n4p308
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo de bovinos jovens mantidos em pasto de sorgo ou milheto

Abstract: ingestivo e os padrões de deslocamento de novilhos de corte mantidos em pastagens de milheto ou de sorgo. Os tratamentos consistiam em: pastagem de milheto ( Leeke) ou pastagem de sorgo ( L. Moench), ambos submetidos à lotação contínua. Foram utilizados 18 novilhos, oriundos do cruzamento entre as raças Charolês e Nelore, com idade média inicial de 14 meses, e peso corporal inicial de 195 kg. O delineamento experimental foi blocos ao acaso com 3 repetições e parcelas subdivididas no tempo em 3 períodos, sendo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
3
0
2
Order By: Relevance
“…Although some studies indicate that supplementation affects the daily number of bites because of the increased nutrient intake via supplementation (Santana et al, 2013;Stivanin et al, 2014), we found no significant differences in this variable between treatments ( Table 2). The movement rate (9.28 and 11.3 steps min -1 ) and the number of stations visited per min (6.99 and 7.33) reported by P. M. Martini et al (2017) and Rodrigues et al (2019) in cattle grazing sorghum were like those of our study.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Although some studies indicate that supplementation affects the daily number of bites because of the increased nutrient intake via supplementation (Santana et al, 2013;Stivanin et al, 2014), we found no significant differences in this variable between treatments ( Table 2). The movement rate (9.28 and 11.3 steps min -1 ) and the number of stations visited per min (6.99 and 7.33) reported by P. M. Martini et al (2017) and Rodrigues et al (2019) in cattle grazing sorghum were like those of our study.…”
Section: Resultssupporting
confidence: 84%
“…This result might have affected the rate of leaf development and the movement rate during the grass growth cycle (Table 2). The sward structure determines leaf and stem height as well as forage availability and accessibility to the animals, and affects feeding selectivity, time spent at each feeding station, and grazing time (Fonseca et al, 2013;P. M. Martini et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Maiores teores de lignina e fibra da pastagem nativa no primeiro período (mês de agosto), explicam maior tempo e número de mastigadas por bolo ruminal regurgitado. Martini et al (2017) também verificaram aumento no tempo de ruminação por bolo alimentar quando o teor de fibra aumentou.…”
Section: Discussionunclassified
“…Due to heterogeneity in grazed swards its structure is changed along time. Sward structure impacts animal movement and distribution, as well as ingestive behavior and daily intake (Mezzalira et al, 2014;Martini et al, 2017). Nitrogen fertilization also can improve dry matter accumulation rate, forage allowance and crude protein level of AG pasture (Martins et al, 2000).…”
Section: Introductionmentioning
confidence: 99%